Neuroprotection and antioxidative effects of Sijunzi Tang Decoction in the nematode Caenorhabditis elegans - Schlotterer, Andrea; Humpert, Per Magnus; Hammes, Hans-Peter; Morcos, Michael (European journal of integrative medicine, 2016)
Introduction - Knowledge about the pharmacological properties of traditional TCM formulas is scarce as is their impact on aging. This study evaluated the potential effects of Sijunzi Tang Decoction (SJZTD), Si-Wu-Tang Decoction (SWTD), and Liuwei Dihuang Decoction (LWDHD) against oxidative stress and glucotoxic stress-induced neuronal dysfunction and lifespan reduction. - Methods - Nematodes (C. elegans) were cultivated under 10mmol/L paraquat or 400mmol/L glucose to assess the protective effects of a systemic Traditional Chinese Medicine (TCM) treatment. Lifespan was determined by calculation of Kaplan-Meier survival curves, formation of reactive oxygen species was quantified by hydroethidine staining, and neuronal functions were evaluated by worm tracking analysis. - Results - A 10% SJZTD solution largely normalized nematode survival under both oxidative stress (increased 3-day-survival rate by 143%) and glucotoxic stress (extended mean lifespan from 19.90 to 23.71 days). Under high glucose conditions we demonstrated both antioxidative effects (reduced Reactive Oxygen Species (ROS) formation by 71%) and neuroprotective effects (improved whole nematode motility by 179%). SWTD and LWDHD failed to confer protection in our model system. - Conclusions - The neuroprotective effects for SJZT decoction against glucotoxic stress due to pronounced antioxidant properties were demonstrated. Future studies should be extended to protection of the neurovascular system in higher organisms.